CONCEPT OF ISLAMIC BUSINESS ETHICS IN MANAGEMENT SHARIA HOTEL IN MAKASSAR CITY (International Conference on Social and Islamic Studies, 2022)
Islamic business ethics concept has begun to be applied in various business sectors. This study to determine Islamic business ethics and its implementation in sharia hotel in Makassar City. This research method is descriptive qualitative at Hotel al-Badar Syariah Makassar with 7 informants. The results found Islamic business ethics is in accordance with the Tauhid concept in worship facilities; the balance concept on the payment of salaries and hotel rates; the free will concept on price promotion strategies, service discounts and non-Muslim guests; the responsibility concept on prayer times reminders, provision of prayer facilities and equipment and excellent service; and the ihsan concept on sharia accommodation support. Implementation it is applied to: rules and hotel names labeled sharia; facilities to support compliance; and services by greeting, being polite in information, responding to complaints, dressing politely, and collaborating with partners labeled sharia. The conclusion of this study is the Islamic business ethics concept is in accordance with the principles of monotheism, balance, free will, responsibility and ihsan, as well as its implementation in sharia hotel management in Makassar City through rules, facilities and services, so that it can become a role model for hotels that want to change be sharia hotel. The implication of this research is that the existence of a sharia hotel can eliminate the impression of negative things attached to the hotel business and the importance of halal certification as a sharia-based business legality.